Pengaruh Alokasi Dana Desa Terhadap Kesejahteraan Masyarakat Desa Batu Kede Kecamatan Masalle - Nur Intan Pratiwi; Andi Mustika Amin; Anwar Ramli; Siti Hasbiah; Anwar Anwar (JURNAL RISET MANAJEMEN (JURMA), 2023)
This research is to find out whether there is an allocation of village funds towards the welfare of the people of Batu Kede village, Masalle District. This research is quantitative research. The sample in this research was the community of Batu Kede Village, Masalle District, totaling 65 families. The hypothesis test in this study used a simple regression test and obtained the results, namely: Based on the results of the hypothesis test using simple regression analysis, it shows that the allocation of village funds has an effect on the welfare of the people of Batu Kede Village, Masalle District.